Characteristics of the Formation of River Slope Run-off in Permafrost Regions (Osobennosti Formirovaniia Sklonovogo Stoka Rek Zony Mnogoletnei Merzloty) - Gopchenko,E D (1978)
This report discusses questions concerning the formation of a slope runoff in the case of a deep lie of the permafrost water confining layer and available length slope thickness of the thaw layer. It is under such conditions that most floods form in mountainous rivers of the northeatern USSR. (Author) Trans. of Meteorologiia, Klimatologiia i Gidrologiia (USSR) v10 p140-144, 1974.